2005
DOI: 10.3346/jkms.2005.20.4.659
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Facet Joint Injections in the Neck and Shoulder Pain

Abstract: The effects from cervical facet joint injections in those patients who have been complaining cervical zygapophyseal joint pain were compared. The patients were diagnosed originally as myofascial pain syndrome (MPS), cervical herniated nucleus pulposus (HNP), and whiplash-associated disorders (WAD). Patients with the zygapophyseal joints pain of C5-6 and C6-7 were classified by their pain origin as MPS, HNP, and WAD. All patients had been undergone cervical zygapophyseal joints injections with the mixture of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 6 publications
(6 reference statements)
1
26
0
Order By: Relevance
“…Neither intervention was associated with a clinically significant pain medication-intake reduction with time. An observational study by Kim et al in 2005 12 suggested that IFSI could be effective in patients with cervical disk herniation. Unfortunately, the study group appeared to be inhomogeneous and the methodology was incompletely described for drawing any sound conclusions from that study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither intervention was associated with a clinically significant pain medication-intake reduction with time. An observational study by Kim et al in 2005 12 suggested that IFSI could be effective in patients with cervical disk herniation. Unfortunately, the study group appeared to be inhomogeneous and the methodology was incompletely described for drawing any sound conclusions from that study.…”
Section: Discussionmentioning
confidence: 99%
“…7 Although the exact prevalence of these devastating adverse events is unknown, some authors have questioned the continued use of TFSI, 8 while others advocate technical strategies to improve the safety of the procedure 9,10 or alternative approaches, which potentially carry fewer risks. 8,11 Preliminary work by Kim et al in 2005 12 and by Richarme et al in 2008 11 suggested that intra-articular facet steroid injections (IFSIs) could be effective in patients with cervical radiculopathy secondary to disk herniation. Anatomically, the facet joint ventral recess is in close proximity to the spinal nerve root.…”
mentioning
confidence: 99%
“…107 In a smaller study in 12 patients with cervicogenic headache that performed empirical radiofrequency denervation without diagnostic injections, 4 of 6 persons in the treatment group experienced success at 3 months, which favorably compared with 2 of 6 in the treatment group. 108 Although small uncontrolled studies have reported benefit with intra-articular corticosteroid injections, 109 the only placebo-controlled study reported no differences between the corticosteroid and local anesthetic control injections at 6-month follow-up. 110 Injections in the form of selective nerve root blocks (SNRBs) have also been advocated as a tool to identify symptomatic spinal levels and select patients for surgery.…”
Section: Injectionsmentioning
confidence: 98%
“…This means that anti-inflammatory drugs may be effective through either systemic administration or local infiltration. Therefore, in the case of inflamed knee joints, as with the diarthrodial joints, it seems more effective to use direct intra-articular injections than Kim, et al innervating nerve branch blocks [8][9][10]. The medial branch also innervates bones, including the posterior lamina and spinous process, ligaments, including the supraspinous ligament, interspinous ligament, and ligament flavum, erect muscles, skin, and subcutaneous tissues, as well as the facet joints [11].…”
Section: ) Nociceptive Painmentioning
confidence: 99%